Strengthening Corporate Legal Functions in Achieving Good Corporate Governance at PT Bank Bengkulu - Siti Aisyah; Widiya N. Rosari; Tito Sofyan (Bengkoelen Justice : Jurnal Ilmu Hukum, 2020)
The increase in company value is reflected in the increase in performance and company image. PT Bank Bengkulu in enhancing the value of the company is done by applying the principles of Good corporate governance supported by the Corporate Legal division. The principles of Good Corporate Governance include: openness, accountability, responsibility, independence and fairness. Corporate Legal functions to regulate matters relating to the legal field which include: Organization and authority, advice or provision of legal assistance andhandling legal cases, risk management and mitigation, documentation, administration and reporting. Previously, Corporate Legal was part of the Compliance Division. However, since the transfer of Corporate Legal to Corporate Secretary, there has been overlapping of authority, duties and functions. The problem in this research is how to strengthen Corporate Legal in realizing Good Corporate Governance and what are the factors that inhibit the strengthening of Corporate Legal function in realizing Good Corporate Governance at PT Bank Bengkulu. This type of research is empirical research, data sources obtained from interviews, documents, as well as literature and legislation relevant to research. The results of the study are the strengthening of Corporate Legal at PT Bank Bengkulu conducted by organizational restructuring based on Directors Decree No.17.1 / HP.00.01 / D.1 / 2019/2019 regarding changes in the organizational structure of the transfer of Corporate Legal to Corporate Secretary which was formerly Corporate Legal part of Compliance division, thistransfer makes Corporate Legal have a wider authority that is able to provide legal oponi which includes external banks where previously in compliance with Compliance, Corporate Legal can only provide legal opinions that cover only the internal parts of the bank. The factor that inhibits the strengthening of the function of Corporate Legal in realizing good corporate governance at PT Bank Bengkulu is the overlapping authority between the Compliance division and the Corporate Secretary, in which there are no restrictions on what should be reviewed by the Compliance Division and Corporate Secretary, then in policytaken by the Board of Directors cannot be immediately decided by Corporate Legal so the problem becomes slow to be resolved immediately.